Routledge handbook of biosecurity and invasive species - Barker, Kezia; Francis, Robert A. (Routledge handbooks, 2021)
"This handbook provides a comprehensive overview of the assessment and management of potentially dangerous infectious diseases, quarantined pests, invasive (alien) species, living modified organisms and biological weapons, from a multitude of perspectives. The issues of biosecurity have gained increasing attention over recent years but hitherto have often only been addressed from narrow disciplines and with a lack of integration of theoretical and practical approaches. The Routledge Handbook of Biosecurity and Invasive Species brings together both the natural sciences and social sciences for a fully rounded perspective on biosecurity, shedding light on current national and international management frameworks with a mind to assessing possible future scenarios. With chapters focussing on a variety of ecosystems, including forests, islands, marine and coastal and agricultural land, as well as from the industrial scale to individual gardens, this handbook reviews the global state of invasions and vulnerabilities across a wide range of themes and critically analyses key threats and threatening activities, such as trade, travel, land development and climate change. Identifying invasive species and management techniques form a regional to international scale, this book will be a key reference text for a wide range of students and academics in ecology, agriculture, geography, human and animal health, and interdisciplinary environmental and security studies"--Provided by publisher.